Application of Cooperative Script with Mind Map Variations as an Effort to Increase Physical Education Students' Interest and Learning Outcomes - Syafrial, Syafrial; Yahya Eko Nopiyanto; Fiona Sarah Musfita; Nurul Fajar Muslimah Ningrum; Sugihartono, Tono (UNIB Press, 2024)
Achievement of learning outcomes is an indicator to measure the quality of the learning process that has been implemented. However, achieving optimal learning outcomes is not an easy thing for lecturers in charge of the subject because many factors influence it, including the learning model and student learning interest while in class. Therefore, lecturers must be able to apply learning models that can increase interest in learning. The application of cooperative scripts with mind map variations as a learning model is feasible to be applied to the adaptive physical education learning process. Classroom action research with 2 cycles was chosen as the research method. The goal to be achieved in this study is to analyze the increased interest and learning outcomes of physical education students through the application of cooperative scripts with variations of mind maps in adaptive physical education lectures. The research data was accommodated using instruments in the form of observation, questionnaires, and written tests. The collected data were analyzed using simple statistics in the form of average values and percentages. The results of the study illustrate that there is an increase in interest in learning and learning outcomes. It can be concluded that cooperative scripts with mind map variations can be an alternative to increase student interest and learning outcomes.